Pulse Wave Calibration and Implications for Blood Pressure Measurement: Systematic Review and Meta-Analysis. Issue 2 (August 2021) - Jedrzejewski, Dawid; McFarlane, Ewan; Lacy, Peter S.; Williams, Bryan
Abstract : Central aortic systolic pressure (CASP) can be estimated via filtering of the peripheral pulse wave (PPW) following calibration to brachial blood pressure. Recent studies suggest PPW calibration to mean arterial pressure (MAP) and diastolic BP (DBP) provides more accurate CASP estimates (CASPMD ) versus conventional calibration to systolic BP (SBP) and DBP (CASPSD ). However, the peak of the MAP-DBP calibrated PPW, that is, SBPMD, is rarely reported or used for BP amplification calculations, despite CASPMD being derived from it. We aimed to calculate the unreported SBPMD from studies using MAP-DBP calibration for estimation of CASPMD and compared it with oscillometric brachial SBP (brSBP). Medline database was searched to March 18, 2020. Meta-analysis includes studies reporting noninvasive CASPSD, CASPMD, brSBP, and brachial DBP. SBPMD was calculated using linear function equations. Data from 21 studies used 8 different BP monitors (13 460 participants, mean age: 54±10 years, 57% female, brachial blood pressure: 130±14/79±9 mm Hg). Weighted mean difference between SBPMD and brSBP was 10 mm Hg (range, −2 to 17 mm Hg) and appeared device specific. Calibration of brachial versus radial PPWs to brachial blood pressure showed a greater disparity between SBPMD and brSBP (14 versus 2 mm Hg). BP amplification was similar comparing SBP-DBP versus MAP-DBP calibrations (brSBP-CASPSD versus SBPMD -CASPMD : 9 versus 11 mm Hg), with no instances of reverse BP amplification. PPWs calibrated to MAP-DBP to derive CASPMD generates SBPMD that differs markedly from brSBP with some oscillometric BP monitors. These findings have important implications for BP monitor accuracy, BP amplification, PPW calibration recommendations, and studies of associations between CASP versus SBP and outcomes. Abstract : Supplemental Digital Content is available in the text.